METODE BRAT DALAM MENURUNKAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Afrianti, Novi; Dewiyuliana, Dewiyuliana; Kamal, Anda (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Hypertension is one of the diseases that often causes various negative effects for sufferers. Uncontrolled hypertension can impair quality of life and interfere with daily activities. It can also harm other organs, including the kidneys, heart, brain, and eyes. Medication can rapidly reduce high blood pressure, but long-term use can have negative effects, such as renal damage. Therefore, using a non-pharmacological method is a simple, affordable, and safe to control blood pressure. Non-pharmacological interventions like the BRAT method can be an aid intervention. This study aims to identify the effectiveness of the BRAT method in reducing blood pressure in patients with hypertension. This study used an experimental research design with a pretest-posttest control group approach. By considering alpha value 0,05, power 80%, and effect size 0,713, G*power analysis was implemented to determine the patients; thus, it was found that 64 patients with hypertension were divided into two groups (each 32 patients). A digital sphygmomanometer was used to measure blood pressure before and after 12 BRAT technique applications. The data was analyzed using the t-test. The results showed that the average systolic blood pressure of hypertensive patients in the intervention group is 144.97 mmHg and the control group is 148.09 mmHg; there is a significant difference (p-value 0.000) between the systolic and diastolic blood pressure readings before and after the Brisk Walking Activity Therapy (BRAT) approach was implemented. It can be concluded that the BRAT method effectively reduces blood pressure in patients with hypertension. This intervention can be an option for patients with hypertension who want to reduce their blood pressure non-pharmacologically.